Differences in Linguists’ Perceptions of the History of Korean Language: Focusing on the Causes - Hyun-Soo Moon (Acta Linguistica Asiatica, 2025)
Differing perceptions of Korean language history exist among South Korean, North Korean, and Korean-Chinese linguists. Notably, they disagree on the timing of Old Korean and Medieval Korean. North Korean scholars place Old Korean into the period from the early 30th century to the 3rd century BC, and Medieval Korean into the period from the 3rd century BC to the 19th century AD. South Korean linguists, however, fit Old Korean into the period from the 4th century to the 10th century AD and Medieval Korean into the period from the 10th century to the 16th century AD. These variations stem from differing research perspectives: South Koreans rely on literary and linguistic sources, while North Koreans emphasize Marxist historical development. Korean-Chinese linguists initially aligned with North Korean views but have shifted due to evolving diplomatic relations between China and South Korea.